2016
DOI: 10.1016/j.biopsych.2015.11.025
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Social Bayes: Using Bayesian Modeling to Study Autistic Trait–Related Differences in Social Cognition

Abstract: Our results demonstrate that higher autistic traits in healthy subjects are related to lower scores in a learning task that requires social cue integration. Computational modeling further demonstrates that these trait-related performance differences are not explained by an inability to process the social stimuli and its causes, but rather by the extent to which participants take into account social information during decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…A secondperson neuropsychiatry, therefore, promises to interrogate those brain systems that subserve active participation in and understanding of social interactions and may provide novel neuroimaging biomarkers of social interaction-based processes that might be both diagnostically and therapeutically helpful across different disorders. Of note, the secondperson approach advocated here draws upon a conceptual framework [3,4] which addresses the importance of being part of a social interaction and the embeddedness in a social environment, but is also open to explore how computational approaches can help to explain the underlying cognitive architecture possessed by individuals in the context of complex social situations [139].…”
Section: Towards a Second-person Neuropsychiatrymentioning
confidence: 99%
“…A secondperson neuropsychiatry, therefore, promises to interrogate those brain systems that subserve active participation in and understanding of social interactions and may provide novel neuroimaging biomarkers of social interaction-based processes that might be both diagnostically and therapeutically helpful across different disorders. Of note, the secondperson approach advocated here draws upon a conceptual framework [3,4] which addresses the importance of being part of a social interaction and the embeddedness in a social environment, but is also open to explore how computational approaches can help to explain the underlying cognitive architecture possessed by individuals in the context of complex social situations [139].…”
Section: Towards a Second-person Neuropsychiatrymentioning
confidence: 99%
“…While this latter study shows the importance of mentalizing for predicting others' actions, it does not show that the predictions about others are also used during strategic decision-making. Assuming that the impact of ToM on predictions and beliefs are identical with its impact on social choices seems farfetched since, as a recent study shows, impairments of social skills do not affect learning or the processing of social cues, but their use in decisions (Sevgi et al [21]). …”
Section: Theory Of Mind As a Central Process For Successful Strategicmentioning
confidence: 99%
“…Consequently, even individuals without a diagnosis of autism differ in the scores on the Autism Quotient (AQ) (Yoshida et al [19]), a well-established psychometric test used to assess autistic traits. In contrast to the notion that high autistic traits are always associated with a ToM deficit, it has been shown that high-functioning individuals with autism show a dissociation of explicit and implicit mentalizing abilities: while they are able to explicitly mentalize what others do and may even spend more time mentalizing than low AQ individuals (Senju et al [23]), they are impaired to form adequate mental representations of the specific other in the ongoing social interaction and to use them during social decision-making (Sevgi et al [21]). …”
Section: Strategic Decision-making and Autistic Traits In Normal Adultsmentioning
confidence: 99%
See 2 more Smart Citations